Menumbuhkembangkan Entrepreneurship Generasi Milenial Muslim Di Era Revolusi Industri 4.0 Dalam Meningkatkan Peradaban Ekonomi Umat - Fahrurrozi Fahrurrozi (Jurnal Ilmiah Ekonomi Islam, 2022)
Currently the development of technology is very rapid, changes in economic civilization have unwittingly experienced an increase that was never stated in the human mind. The industrial revolution 4.0 is a concrete example of this change in economic civilization. Industrial Revolution 4.0 is an industry that combines automation technology with cyber technology. This is a trend of automation and data exchange in manufacturing technology. This includes cyber-physical systems, the Internet of Things (IoT), cloud computing and cognitive computing. This is an opportunity as well as a challenge for millennials, because this millennial generation is better able to take advantage of this opportunity. The methodology used by researchers (qualitative methodologies with interpretive and critical approaches) has the aim to be able to give meaning to fostering entrepreneurial character in the Muslim milleneal generation by using the divine values approach that is full of transindental and theological, researchers have the aim to be able to contribute thought which is beneficial to the millennial generation of Muslims in growing and developing the spirit of entrepreneurship by being principled in Islamic moral principles and morals and avoiding moral integration and decadence that lately is experienced by many generations today.